KRITIK SOSIAL DAN SENI VISUAL DALAM TINJAUAN FEMINISME KULTURAL - Adityari, Arti Dewi Sri Maharani; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This study explains Balinese culture's social criticism in visual artworks by Citra Sasmita. Sasmita uses social issues in Bali, especially those related to women. This study was conducted on cultural feminism using descriptive qualitative research methods with observation, interviews, and documentation to collect data. This research shows that the combination of ideas and visuals with universal language in Sasmita's works can be accepted and supported by the public, even though she initially received much criticism in her early career. This opportunity is due to the opening of space and opportunities for female artists and to public awareness, which has begun to be open to understanding gender equality and the recognition of women in public space. Future female artists are expected to be freer to work with their ideas without thinking about the burden of selling their artwork.